Regional Quality and Impaired Firms: Evidence from Italy - Angela De Martiis; Jarko Fidrmuc (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We analyze how regional quality affects firm's efficiency by identifying the impaired firms receiving financial assistance as those paying an implicit interest rate lower than the prime rate. Then, we decompose them into: real impaired firms unable to repay their loans, and those not repaying their debts even if financially they could. The regions with a high share of loans and crime exhibit a higher concentration of distressed firms, and crime increases the performance of existing companies.
Keywords: O43; E51; G33; 330